Produção e caracterização de nanocompósitos híbridos de nanotubos de carbono e dolomita em poliéster para aplicação em dispositivos de sinalização viária - Felipe Luiz Queiroz Ferreira (2017)
This work focused on the improvement in the performance of unsaturated polyester adhesives used to fix road markers devices. A partnership with the company Vialit was established to carry out this research, which experiments were initially designed to optimize the formulation of polyester and then, high performance adhesives based on hybrid nanocomposites of polyester, dolomite and carbon nanotubes were produced. In the first part of the study, the influence of the proportion of initiator and dolomite additive used in the formulation was evaluated, making it possible to obtain adhesives with properties much higher than previously used. For example, shear strength more than doubled as observed by the lap shear tests, tensile strength increased by 32% and stiffness also increased significantly. An evaluation of the dolomite amount in the composites showed the influence of this additive on the mechanical properties of the adhesive, and the increase in the amount of filler used decrease properties like toughness, tear strength and specific deformation of the polyester. This result reinforces the need to weigh the cost versus adhesive properties.The incorporation of carbon nanotubes to the polyester adhesive showed that small amounts of carbon nanotubes (up to 0.30% by mass) increased the stiffness and toughness of the adhesive, indicating that hybrid nanocomposites may bring better mechanical properties to the road markers devices. A further study with new strategies of nanotube processing and functionalization can be tested in future experiments to complement the results of this work